Enzymatic synthesis of glucuronidated metabolites of two neurological active agents using plant glucuronosyltransferases. Issue 7 (3rd July 2018) - Yue, Tian; Xie, Ke-Bo; Tan, Zhen; Chen, Ri-Dao; Chen, Da-Wei; Liu, Ji-Mei; Dai, Jun-Gui
Abstract: Glucuronidation is an important and popular metabolic reaction in vivo of drugs. The further evaluation of biological activity and toxicity of glucuronides is necessary in the course of the drug research and development. However, the synthesis of glucuronides is limited by the lack of efficient approach. Herein, we have developed a new glucuronide synthesis method using plant uridine diphosphate-dependent glucuronosyltransferases (UGTs), UGT88D4, UGT88D7, and EpGT8, enabling the convenient preparation for corresponding O -glucuronide metabolites (1a, 2a, 3a, and3b ) in milligram scale of two neurological active agents, IMM-H004 (1 ) and FLZ (2 ). Their structures were characterized by spectroscopic data analyses. Abstract :